Solitary Adrenal Metastasis from Esophageal Adenocarcinoma: A Case Report and Review of the Literature. (19th October 2011) - Dellaportas, D.; Lykoudis, P.; Gkiokas, G.; Polymeneas, G.; Kondi-Pafiti, A.; Voros, D.
Abstract : Introduction . In patients with extra-adrenal malignancy, an adrenal mass necessitates investigating the possibility of metastatic tumor. Curable adrenal metastasis are considered as a rare event. Case report . A 52-year-old male suffering from lower esophageal adenocarcinoma with a solitary left adrenal metastasis is presented herein, who underwent concomitant transhiatal esophagectomy and left adrenalectomy. The patient remains disease-free 18 months later. Discussion . Adrenal metastases mostly occur in patients with lung, kidney, breast, and gastrointestinal carcinomas. Primary esophageal adenocarcinoma gives adrenal metastatic deposits according to autopsy series with an incidence of about 3%–12%. When no other evidence of metastatic disease in cancer patients exists, several authors advocate adrenalectomy with curative intent. Isolated cases of long-term survival after resection of solitary adrenal metastasis from esophageal adenocarcinoma, like in our case, have been reported only as case reports. Conclusion . This study concludes that surgical resection may result in survival benefit in selected patients with solitary adrenal metastasis from esophageal adenocarcinoma.